Recharge App Pengembangan Aplikasi Pencari (Tracking) Untuk Isi Ulang Baterai Motor Listrik - Dzikri, Muhammad Wildan; Arifian, Tesar Agnia; Sahara, Siti (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This study aims to provide information about battery recharge locations through the Recharge App. The research method employed is Research and Development (RnD) using the 4-D model (Define, Design, Develop, and Disseminate). Research tools and instruments include surveys, interviews, as well as frontend and backend development devices. The research findings indicate a user satisfaction rate of 90%. However, some features such as notifications and sharing functions require further development. Limited launch through social media platforms and user feedback are utilized to guide further development. This study demonstrates the significant potential of the application in providing beneficial information services, yet further refinement is necessary to achieve optimal functionality in meeting users’ needs comprehensively.